Comparative Analysis of The Effect of Epoxy Silicone Rubber Resin with Silica Sand/TiO 2 and Silica Sand/MgO Fillers on The Mechanical and Electrical Characteristics of Insulators - Yulianta Siregar; Rut Daniela Ginting; Issarachai Ngamroo (My University, 2025)
Epoxy resin-based insulators are the latest innovation in the development of insulating materials. Epoxy resin insulators made of silicone rubber with fillers can increase the reliability of insulating materials used in high-voltage transmission. Adding fillers such as silica sand and TiO2 and MgO nanoparticles can increase the insulator's electrical strength and mechanical strength. This study shows that the best mixture composition to increase the value of volume resistivity, surface resistivity, dielectric strength, compressive strength, and tensile strength, reviewed in terms of economy, is the S9 test sample. The composition of S9 consists of 30% MPDA resin, 30% DGEBA resin, 20% silica sand, 15% silicone rubber, and 5% MgO. This sample shows a volume resistivity value of 0.313 MΩm, surface resistivity of 74.593 MΩm, dielectric strength of 116 KV/cm, compressive strength of 41 kN, and tensile strength of 5.260 MPa.
Keywords: High voltage insulation and dielectric phenomena; Aerogels and thermal insulation; Polymer Nanocomposites and Properties